Manliness as a virtue of a conscious homosexual in 1930s (Theatrum historiae, 2009)
In this contribution, I approach the question of how and why the homosexuals in Czechoslovakia reflected, in the 30s of the 20th century, the way they were seen by the majority society, focusing on the polarity manliness-femininity. The medical discourse on homosexuality was, from its beginnings in the last third of the 19th century, very marked by references to this polarity: the effeminacy in homosexuals constituted a favourite topic of this discourse. The journalism was adding the public image of the homosexual with other characteristics, supporting and nourishing a wide- spread notion of the homosexual as an effeminated, depraved and criminal being. In the the 30s of the 20th century the Czechoslovak homosexuals, willing to improve their social status, founded a magazine, the Hlas sexuální menšiny. I use this magazine as my principal documentary basis to discuss the above mentioned questions. On the pages of the Hlas, we can observe a gradually increasing tendency to keep aside the original goal to obtain the decriminalization of homosexuality and, instead, to accomplish at first a change in the behaviour of homosexuals themselves. The homosexual activists acted on the assumption that only after the negative public image of the homosexual is modified, would it be possible to ask seriously for a decriminalization. Denouncing the effeminacy in male homosexuals (and the masculinity in female ones) and urging their readers to get rid of these features in the name of a homosexual respectability, they were reproducing the stereotypes connected to the traditional system of the gender roles distribution and claiming their validity also for the homosexual milieu.